KAJIAN YURIDIS PERLINDUNGAN HUKUM TERTANGGUNG PADA PERJANJIAN ASURANSI KENDARAAN BERMOTOR DI PT. ASURANSI RAMAYANA TBK. JAKARTA - Novianta Budi Surana (Jurnal Idea Hukum, 2016)
The legal protection for the insured in an insurance agreement with PT Asuransi Ramayana Tbk exists while being observed generally by insurance law for the fulfillment of rights and obligations of both the insured and the insurer. In case of force majeur (unsure occurance) which causes loss; then based on Indonesian Standard Insurance Policy for Motor Vehicle Chapter 1 Article 1 and Article 2, the insured deserves to get the indemnity due to theft, and also get the solution for the dispute through a mediator under Article 54 Chapter XI 40 of 2014 concerning insurance about the protection of Insurance Policy holders, the Insured or the participant. The refusal of legal validity of the claim by PT. Asuransi Ramayana Tbk is not appropriate and does not have any correlation with the case of theft occurred because in Mr. Mery Sam Arvianto’s case, the insurance agreement with the insurance policy number 18.0212.14.001512 must covers All Risk / Comprehensive ( collateral damage to a part or the whole car because of falling objects, fire, collision, traffic accidents, theft or collision), and the insured should receive compensation, based on Chapter 1 Article 1 paragraph 1.3 Indonesian Standard Policy for motor vehicle insurance governing the guarantee, including guarantee from theft.Key Words: The legal protection for the insured in an insurance agreement.